Supplier Development Practices and Supply Chain Performance of County Governments in Kenya - Otieno, Kevin; Odero, Jackline Akoth (Rescollacom (Research Collaborations Community), 2024)
Many organizations have realized the significant role suppliers play in determining organizational performance. This study sought to examine the influence of supplier development practices on supply chain performance of County Governments in Kenya. This study employed a descriptive survey research design targeting 112 procurement staff. The study utilized both stratified and simple random techniques. For data collection close ended questionnaires was used. For data analysis descriptive and inferential statistics were used. Descriptive statistics used were mean and standard deviation and Inferential statistics used Pearson correlations and simple linear regression. The study found that supplier development practices had a positive and significant effect on supply chain performance of County Governments in Kenya. The findings extends our knowledge on supplier development practices that can enhance performance. The study recommends for County Governments to develop suppliers through training, supplier financing and innovation so as to enhance performance of supply chain.